The Strategy And Role Of Sultan Amai's Da’wa During The Development Of Islam At Gorontalo - Dian Adi Perdana; Junaedy Abdullah; Fatmawaty H. Usman; Fikri Makalunsenge; Rusnan Chema (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2025)
Sultan Amai is known as the founder of the Islamization of Gorontalo. This study is so important and interesting to explore more deeply because of his character. The purpose of this study was to determine the strategy and role of Sultan Amai's da'wah in Gorontalo and to determine the development of Islamic da'wah during his leadership. This research is a descriptive qualitative research with data collection techniques namely observation, interviews and documentation, which then the data that has been obtained is then studied, analyzed and interpreted in order to facilitate in drawing conclusions. The results of this study indicate that Sultan Amai's da'wah strategy in spreading Islam to the people of Gorontalo is through marriage, politics, building a network of Gorontalo clerics, and art as a medium of da'wah to the community. The Islamization of Gorontalo developed because of his role as king and the Islamic preacher of Gorontalo. The non-coercion, friendliness and civility carried out by Sultan Amai in preaching which is made into the principles of the life of Syara' which is customary, and the customs that are required.